Humanitarian Logistics in Post-Disaster Response: Lessons from the 2018 Earthquake and Tsunami in Palu and Donggala - Primadi, Andri; Yosepha, Sri Yanthy (Logistica : Journal of Logistic and Transportation, 2024)
The increasing frequency of natural disasters highlights the importance of efficient humanitarian logistics in post-disaster response. This study examines the logistics challenges and adaptive responses during the 2018 earthquake and tsunami in Palu and Donggala, Indonesia. Interviews with 10 key stakeholders including national agencies, NGOs, military units, and local volunteers were analyzed using thematic analysis. Four themes emerged: infrastructure vulnerabilities, adaptive logistics strategies, multi-actor coordination, and system improvement. Findings show that damaged infrastructure and inconsistent survivor data significantly delayed aid distribution. However, adaptive responses such as drone mapping, logistics hubs, and helicopter drops mitigated accessibility barriers. Coordination improved in later phases through joint command posts and national logistics platforms. The study emphasizes the need for integrated logistics information systems and community-based preparedness to strengthen supply chain resilience. Limitations include the small sample size and localized scope, suggesting that future research should involve broader comparative studies across different disaster contexts. This research contributes to humanitarian logistics literature by providing grounded insights into the interplay of systemic risk, adaptive response, and governance in a complex disaster setting.